Sensory Eating Problems Scale (SEPS) for children: Psychometrics and associations with mealtime problems behaviors. (1st February 2019) - Seiverling, Laura; Williams, Keith E.; Hendy, Helen M.; Adams, Whitney; Yusupova, Stella; Kaczor, Aleksandra
Abstract: The present study developed the 22-item Sensory Eating Problems Scale (SEPS) to measure sensory aspects for children surrounding eating, documented psychometrics of SEPS subscales, and examined their association with mealtime behavior problems. Study participants were 449 caretakers of children referred to feeding clinics, including children in three special needs status groups: autism spectrum disorder (ASD), other special needs, and no special needs. Caretakers completed surveys to report children's demographics, four measures of children's mealtime behavior problems, and five-point ratings for how often children showed various sensory feeding reactions. Exploratory factor analysis of the sensory feeding items identified six SEPS subscales with acceptable goodness-of-fit, internal reliability, and test-retest reliability: Food Touch Aversion, Single Food Focus, Gagging, Temperature Sensitivity, Expulsion, and Overstuffing. ANCOVAs revealed that child demographics most associated with higher SEPS subscale scores were younger age and special needs. Multiple regression analyses found that children's mealtime behavior problems were most often associated with SEPS subscales of Food Touch Aversion, Single Food Focus, Expulsion, and Overstuffing, with the set of six subscales explaining 18–44% of variance in mealtime behavior problems. Suggestions for how clinicians and researchers may find the SEPS useful for assessment and intervention are provided.